Small invertebrate consumers produce consistent size spectra across reef habitats and climatic zones. Issue 1 (5th November 2020) - Fraser, K. M.; Stuart‐Smith, R. D.; Ling, S. D.; Edgar, G. J.
Abstract : Changes in invertebrate body size‐distributions that follow loss of habitat‐forming species can potentially affect a range of ecological processes, including predation and competition. In the marine environment, small crustaceans and other mobile invertebrates ('epifauna') represent a basal component in reef food webs, with a pivotal secondary production role that is strongly influenced by their body size‐distribution. Ongoing degradation of reef habitats that affect invertebrate size‐distributions, particularly transformation of coral and kelp habitat to algal turf, may thus fundamentally affect secondary production. Here we explored variation in size spectra of shallow epifaunal assemblages (i.e. the slope and intercept of the linear relationship between log abundance and body size at the assemblage level) across 21 reef microhabitats distributed along an extensive eastern Australian climatic gradient from the tropical northern Great Barrier Reef to cool temperate Tasmania. When aggregated across microhabitats at the site scale, invertebrate body size spectra (0.125–8 mm range) were consistently log‐linear (R 2 ranging 0.87–0.98). Size spectra differed between, but not within, major groups of microhabitats, and exhibited little variability between tropical and temperate biomes. Nevertheless, size spectra showed significant tropical/temperate differences in slopes for epifauna sampled on macroalgal habitats, and in elevation for soft coral and sponge habitats. Our results reveal epifaunal size spectra to be a highly predictable macro‐ecological feature. Given that variation in epifaunal size spectra among groups of microhabitats was greater than variation between tropical and temperate biomes, we postulate that ocean warming will not greatly alter epifaunal size spectra directly. However, transformation of tropical coral and temperate macroalgal habitats to algal turfs due to warming will alter reef food web dynamics through redistribution of the size of prey available to fishes.